ANALISIS PERHITUNGAN PAJAK PENGHASILAN PASAL 25 PADA PT. SURYA FAJAR MAS MANADO - Mamahit, Ryan Yngwie; Sabijono, Harijanto; Walandouw, Stanley Kho (Universitas Sam Ratulangi, 2020)
Tax is main source of revenue for financing all govermental expenditures, both in terms of development and activities related to the interests of the country. Used also for general fund expenses related to the duty of the state to govern. PT. Surya Fajar Mas is a company engaged in the construction field. Company made tax payments, one of which is that the corporate income tax income tax Article 25. This study aims to determine the calculation, depositing, and reporting of income tax Article 25 on PT. Surya Fajar Mas. This study used a quantitative study. The result shows that the calculation of income tax artile 25 at PT. Surya Fajar Mas was correct and in correcting the fiscal in accordance with the applicable tax laws. It is recommended that both operasional and administrative and general as well as other expenses should be substantiated with strong and valid evidance.